PROSPECTS OF RNA-INTERFERENCE IN THE TREATMENT OF HIV-INFECTION - Чернікова, Л.І.; Коваленко, Н.І. (World of Medicine and Biology, 2015)
HIV infection is an important public health problem all over the world. Despite the advances made in the treatment of HIV infection the prevention of infection and overcome the resistance of the virus to antiretroviral drugs remain outstanding. The article presents a literature review of studies on possible usage of RNA interference in the treatment of HIV infection. Cell cultures, genetically modified mice with transplanted human cells, primates are used in the research. The mechanism of RNA interference is a double-stranded RNA induction of recognition and degradation of cellular mRNA processes. These processes lead to the reducing of expression (silencing) of the gene. The discovery of RNA interference makes it possible to block activity of undesirable genes without any interference in the genome, directing its own protective apparatus of cells RISC to a messenger RNA, thus blocking the synthesis of undesirable product. Properly designed interfering RNA fragment can "eliminate" unnecessary gene and in this ways stop the progressing of the disease at an early stage. Clinical studies of using RNAi are conducted in the treatment of AIDS. Ways to influence on different stages of HIV replication in the already infected cells (in particular on the stages of integration, assembly and release of virus from cells) have been developing as well as to block the synthesis of co-receptors CXCR4 and CCR5 of human cells to preventing of penetration of the virus. Ability of interfering RNA to reduce replication for HIV in cell culture of human lymphocytes at the stage of proviral DNA synthesis was proved. The possibility of resistance in sensitive cells to R5 HIV strains as in vitro, and in laboratory animals was proved. Also the stable expression of siRNA, which can block the synthesis of co-receptors CCR5 and viral replication was shown. These siRNAs are introduced into the body of patients with AIDS by transplantation of hematopoietic stem cell progenitors. Interfering RNAs that inhibit the synthesis of the reverse transcriptase of HIV-1 have been used to overcome the resistance of the virus to lamivudine. Share lamivudine and siRNA suppressed the replication of the mutant virus strain resistant to this drug. To prevent undesirable side reactions safe methods of selective delivery of interfering RNAs to infected cells using synthetic antibodies, lentivirus vector or transplantation of hematopoietic stem progenitor cells which express siRNA are developed. Thus, new methods of overcoming HIV can be used to treat patients for whom a standard antiretroviral therapy wasn’t successful.